Mutual acoustic impedance of cylindrical sources for a specific case - Witold RDZANEK (Archives of Acoustics, 2016)
The paper analyzes the imaginary component of the mutual impedence of two pulsating cylindrical rings placed on an infinitely long and stiff circular cylinder. The specific case of the radius of the cylinder being considerably shorter than the wave lengths of the acoustic waves radiated is considered. The imaginary component of the mutual impedence was calculated using the HILBERT transformation, based on the approximate expression for the real component of the mutual impedance given by ROBEY. Compared to earlier results the formulae have a simple form, and are thus convenient for numerical Calculations. These calculations are illustrated graphically.